2018
DOI: 10.1016/j.numecd.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and ventricular-vascular coupling in hypertensive patients with metabolic syndrome

Abstract: Background and aims: Metabolic syndrome (MetS) is currently considered to raise the risk for type 2 diabetes and cardiovascular events. It has been suggested that part of this risk excess may be due to a cluster of additional factors associated with MetS. We aimed to investigate the role of inflammation on the ventricular-vascular coupling in patients with MetS. Methods and results: We enrolled a total of 227 hypertensive patients (106 with MetS and 121 without MetS) matched for age and gender. Aortic pulse wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…Furthermore, although circulating concentrations of TNF-α, and IL-6 independently associate with concentric LV remodeling, there is no relationship between these molecules and LVM [30]. Although C-reactive protein may in-part explain ventricularvascular coupling [22], the relationships between resistin and LVM in the present study were independent of Creactive protein. Hence, it is unlikely that the resistin-LVM relationships can be explained by general inflammatory effects.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, although circulating concentrations of TNF-α, and IL-6 independently associate with concentric LV remodeling, there is no relationship between these molecules and LVM [30]. Although C-reactive protein may in-part explain ventricularvascular coupling [22], the relationships between resistin and LVM in the present study were independent of Creactive protein. Hence, it is unlikely that the resistin-LVM relationships can be explained by general inflammatory effects.…”
Section: Discussioncontrasting
confidence: 61%
“…As it is uncertain whether associations between circulating resistin concentrations and adverse cardiac effects may be accounted for by indirect (renal dysfunction or ventricular-vascular coupling) or direct effects, in the present study we assessed the extent to which independent relationships between circulating resistin concentrations and LVM in a large community-based sample are explained by an impact of resistin on renal or aortic function. Furthermore, as general inflammation (as indexed by circulating C-reactive protein [CRP]) may inpart explain the relationship between aortic stiffness and LVM (ventricular-vascular coupling) in hypertensive patients with metabolic syndrome [22], we assessed whether relationships between circulating resistin concentrations and LVM in a large community-based sample are independent of CRP.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a strong association has been reported between visceral adipose tissue and greater serum levels of cytokine, such as leptin, interleukin-6, plasminogen activator inhibitor-1, all of which are related both to endothelial dysfunction and hypertension [21,22,23]. The inflammation pattern promoted by cytokines release is involved in an inflammation-dependent aortic stiffening [24] and it can also lead to left ventricular stiffness and mass increase [24]. This hypothesis is well described in the clinical model of metabolic syndrome [24].…”
Section: Mechanisms Linking Obesity To Hypertensionmentioning
confidence: 99%
“…The inflammation pattern promoted by cytokines release is involved in an inflammation-dependent aortic stiffening [24] and it can also lead to left ventricular stiffness and mass increase [24]. This hypothesis is well described in the clinical model of metabolic syndrome [24]. Moreover, all the components of metabolic syndrome are shown to be related to augmented carotid-femoral pulse wave velocity [25,26], whereas the same relation cannot be described with the cardio-ankle vascular index [25].…”
Section: Mechanisms Linking Obesity To Hypertensionmentioning
confidence: 99%
“…Watanabe et al reported that even in the absence of diabetes and hypertension, MetS is an independent risk factor for AF [38]. Zanoli et al reported significant correlation between high-sensitive C-reactive protein (hsCRP) to atherosclerosis and arterial stiffness reflected by intima-medial thickness and aortic pulse wave velocity, respectively [39]. They suggested that MetS is characterized by an inflammation-dependent acceleration in cardiovascular ageing, which can lead to vascular dysfunction, and would contribute to make patients with MetS more susceptible to atrial remodeling [39].…”
Section: Mets Is a Major Risk For Atrial Cardiomyopathy And Afmentioning
confidence: 99%